ANALISIS PENYERAPAN TENAGA KERJA PADA SEKTOR USAHA KECIL DAN MENENGAH (UKM) DI KOTA SEMARANG - Setiawan, Achma Hendra (JEJAK: Jurnal Ekonomi dan Kebijakan, 2010)
Small and medium enterprises (SMEs) is not only contributing to the economy of a nation but also provide a very large role in terms of employment. This study aimed to analyze the influence of the variable business units, the value of the investment, the value of output and wages to the number of workers at the SMEs sector in the city of Semarang and also analyzes the variables that affect the most dominant of employment in the SMEs sector in the city of Semarang. Data used in this research is secondary data. Data analyzes tools used in this research is multiple regression model with the ordinary least square method in the form of natural logarithms and used the times series data during the period 1993-2007. Based on data processing, it can be obtained the determination coefficient (R2) of 0.806. It means that 80.6 percent of employment changes at the SMEs sector in the city of Semarang can be explained by variations in the number of business units, the value of the investment, the value of output and the cityâs minimum wage, and the rest of 19.4 percent described by other variables outside the model. Overall, the number of business units, the value of the investment, the value of output and the cityâs minimum wage had a significant effect on the employment changes in SMEs. Partially, the independent variables were also significant, except for the variable of output value. That variable did not significantly affect the absorption of labor at the SMEs sector. The variable that most affect the absorption of labor in the SMEs sector in the city of Semarang was the number of business units, while the variable of output value had the least affect among the other independent variables.